Mucosal-dominant pemphigus vulgaris in a captopril-taking woman with angioedema - Justyna Gornowicz-Porowska; Marian Dmochowski; Pawel Pietkiewicz; Monika Bowszyc-Dmochowska (Sociedade Brasileira de Dermatologia, 2015)
AbstractWe describe a 39-year-old woman with an apparent captopril-induced, contact mucosal-dominant pemphigus vulgaris and angioedema, who took captopril during a bout of arterial hypertension. This exposure suggests that captopril and pathophysiology of angioedema stimulated the development of pemphigus vulgaris, which was diagnosed using the novel, indirect immunofluorescence BIOCHIP mosaic, with the modification to detect serum IgG4 autoantibodies. We discuss the patient, who experienced a chain of events leading to the active stage of pemphigus vulgaris, and review concepts of pemphigus vulgaris inducible by drugs and pathological immunity.